A Nationwide Population-Based Study of Corrosive Ingestion in Taiwan: Incidence, Gender Differences, and Mortality - Chuan-Mei Chen; Yueh-Chin Chung; Li-Hung Tsai; Yi-Chen Tung; Horng-Mo Lee; Mei-Ling Lin; Hsin-Li Liu; Woung-Ru Tang (Gastroenterology Research and Practice)
Corrosive injury results from the intake of corrosive-acid-based chemicals. However, this phenomenon is limited to a small number of cases and cannot be extrapolated to the epidemiology of corrosive injuries in actual situations. This study focuses on the annual incidence of corrosive injury and its connection to gender, risk factors, and in-hospital mortality. All patients with corrosive injury (ICD-9 947.0–947.3) were identified using a nationwide inpatient sample from 1996 until 2010. Chi-squared tests and multivariate logistic regression were used to examine risk factors of gender differences and in-hospital mortality of corrosive injury. Young adults comprised the majority of patients (71.2%), and mean age was 44.6 ± 20.9 years. Women showed a higher incidence rate of corrosive injuries, age, suicide, psychiatric disorder, and systemic complications compared with men (p<0.001). The present study demonstrated that age (OR = 10.93; 95% CI 5.37–22.27), systemic complications (OR = 5.43; 95% CI 4.61–6.41), malignant neoplasms (OR = 2.23; 95% CI 1.37–3.62), gastrointestinal complications (OR = 2.02; 95% CI 1.63–2.51), chronic disease (OR = 1.30; 95% CI 1.08–1.56), and suicide (OR = 1.23; 95% CI 1.05–1.44) were strongly associated with in-hospital mortality. Educational programs may be helpful for reducing the incidence of ingestion of corrosive chemicals.